READING AND ANALYSIS OF A WORK OF FICTION AT THE UNIVERSITY - Ш. Р. Абдулахадова (Web of Journals Publishing, 2024)
This article discusses modern technical means and information technologies that play a key role in modern education. Technical means provide convenience and efficiency in the learning process. A variety of activities, such as working with key words, tasks of various kinds, illustrations and expressive reading, contribute to a deep understanding and comprehension of the work.
Keywords: learning, problem, analysis, research, efficiency, thinking, search, analyze.